Strategic management term paper - Bautista, Eric A. (Animo Repository, 1998)
Transport Ship Management, Inc. (TMSI) is a company engaged in management of a ships overall operation. The objective of this term paper is to come-up with strategies for TSMI. In arriving at the strategies of the company, the first step was to define the environment where TSMI belongs and analyze it using Porters five forces model. From the environment, opportunities and threats can be derived. TSMIs opportunities are the increase in market base and manpower availability while threats are emergence of higher shipping technology and being a deregulated support service industry. The companys strengths and weaknesses are derived from analyzing the companys financial statements and value chain. TSMIs strengths are management style, standardized processes, and established relationship with affiliates. Its weaknesses are lack of document of compliance in other service type vessels and poor receivable collection. The basis of a companys strategy is its external opportunities and threats and internal strengths and weaknesses. In strategy formulation, TSMIs vision was developed as quality and safety are its core values. Objectives were set from the developed vision. Formulate corporate strategies develop are application for document of compliance for liquid cargo/lighterage, passenger ferry, passenger cargo, and general cargo operations, higher shipping technology training, and utilizing excess supply of manpower to address TSMIs lack of expertise. Competitive advantages are derived from activities done by the company that give value to customers. Strategies are also formulated at the functional level of marketing, finance, MIS, operations, and HRD. The implementation of these strategies was made using the Sven-S framework. Financial projections were made at the end of the term paper to justify all proposed strategies and to determine if set objectives are attainable.